An exploration of education professionals' construing in relation to student attachment style - Page, Claire (2011)
This study employed a Personal Construct Theory approach (Kelly, 1955/63) to explore education professionals' construing regarding behaviours of secondary-age students representative of the four main patterns of Attachment - 'Avoidant', 'Ambivalent', 'Disorganised' and 'Secure' (Ainsworth & Wittig, 1969; Main & Solomon, 1986; cf attachment theory, Bowlby, 1969; 1973; 1980). Constructs were elicited during individual interviews and rated by participants on a 7-point scale within a repertory grid. Analysis of grids was undertaken in terms of content (the words generated) and structure (the relationships between constructs and elements shown by numerical ratings) (Jankowicz,2004).